Electronic surface, optical and electrical properties of p – GaN activated via in-situ MOCVD and ex-situ thermal annealing in InGaN/GaN LED - Mahat, Mohamad Raqif; Talik, Noor Azrina; Abd Rahman, Mohd Nazri; Anuar, Mohd Afiq; Allif, Kamarul; Azman, Adreen; Nakajima, Hideki; Shuhaimi, Ahmad; Abd Majid, Wan Haliza (Elsevier, 2020)
Electronic surface properties, optical and electrical characteristics of p-type Mg-doped Gallium Nitride (p-GaN) activated under different thermal annealing condition were investigated. In this work, p-GaN samples were subjected to in-situ and ex-situ thermal annealing process at 650 °C in Nitrogen (N2) rich condition. In-situ annealing process took place in Metal Oxide Chemical Vapor Deposition (MOCVD) chamber while ex-situ annealing process was carried out in the conventional oven. X-Ray and Ultraviolet Photoemission Spectroscopy (XPS/UPS) were used to observe the energy alignment of the p-GaN surface. From PES spectra, the sample subjected to in-situ thermal annealing shown to exhibit lower surface bend bending of 0.28 eV as compared to ex-situ thermal annealing activation with 0.45 eV band bending. This result is in agreement with specific contact resistance measurement that shows in-situ sample exhibits lower resistance resulted in better carrier injection from metal to p-GaN. Photoluminescence (PL) spectra elucidates that in-situ sample has a good surface quality with less nitrogen related vacancies (VN) formed on the p-GaN surface. All these results are further proved with the higher output power from LED with in-situ annealing. At 20 mA, in-situ sample shown an increment of ~14% light output power compared to ex-situ sample. Results obtained in this work suggest that the thermal activation condition for p-GaN activation process plays an active role on the surface quality as well as the energy alignment of the film surface and shows the potential of in-situ p-GaN activation for tunnel junction structure. © 2019 Elsevier Ltd